2021
DOI: 10.3390/ph14111149
|View full text |Cite
|
Sign up to set email alerts
|

Ketogal Safety Profile in Human Primary Colonic Epithelial Cells and in Mice

Abstract: In our previous studies, a ketorolac–galactose conjugate (ketogal) showed prolonged anti-inflammatory and analgesic activity, causing less gastric ulcerogenic effect and renal toxicity than its parent drug ketorolac. In order to demonstrate the safer profile of ketogal compared to ketorolac, histopathological changes in the small intestine and liver using three staining techniques before and after repeated oral administration in mice with ketorolac or an equimolecular dose of its galactosylated prodrug ketogal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…We applied the galactosylated prodrug strategy to a number of NSAIDs. The first successful example of this approach was Ketogal [ 25 ], with ACEgal and PARgal then following [ 26 , 27 ]. In each study, the galactosylated prodrug showed marked improvements, compared with its parent drug, in some or all of its physicochemical, pharmacokinetic, pharmacodynamic and toxicological parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We applied the galactosylated prodrug strategy to a number of NSAIDs. The first successful example of this approach was Ketogal [ 25 ], with ACEgal and PARgal then following [ 26 , 27 ]. In each study, the galactosylated prodrug showed marked improvements, compared with its parent drug, in some or all of its physicochemical, pharmacokinetic, pharmacodynamic and toxicological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Promising results have been obtained with the prodrug approach when using D-galactose as a carrier for NSAIDs. In our previous studies, the conjugation of a galactose molecule with ketorolac (Ketogal) [ 25 ], paracetamol (PARgal) [ 26 ] and aceclofenac (ACEgal) [ 27 ] improved their physicochemical, toxicological, pharmacokinetic and pharmacodynamic profiles, resulting in remarkable safety profiles. In particular, the prolonged pharmacological action of the aforementioned prodrugs, in comparison with their parent drugs, would allow their daily intake to be reduced, while also decreasing side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Significant advancements have also been made in the development of galactosylated prodrug derived from the potent NSAID ketorolac. Recent studies by Russo et al (2017) and Sodano et al (2021) have demonstrated that Ketogal, the galactosylated prodrug of ketorolac, exhibits lower toxicity in the stomach, kidney, small intestine, and liver compared to ketorolac [ 28 , 29 ]. In vivo and ex vivo experiments conducted on mice have consistently shown that repeated administration of Ketogal induces reduced toxicity in these organs, supporting its potential as a safer alternative to ketorolac.…”
Section: Galactose For Drug Deliverymentioning
confidence: 99%
“…Each block was immediately fixed in 4% PFA for 24 h at 4 • C. Samples were then processed for wax embedding according to [68], and serial sections (5 µm) were cut. Hematoxylin-eosin staining was used to highlight the general morphology; periodic acid-Schiff (PAS) was used to underline mucin, glycogen and glycoproteins [69]; and the alternative PAS/diastase was performed to highlight all the PAS-positive substances except for the glycogen, that is, digested by diastase, while PAS/dimedone (5,5-dimethyl-1,3-cyclohexanodione) was used to specifically identify the glycogen. Dimedone, in fact, digests all the other PAS-positive substances.…”
Section: Histological Analysesmentioning
confidence: 99%